Pendampingan Pendirian UMKM Olahan Tahu di Dusun Cerme, Desa Gentong, Ngawi, Jawa Timur - Ardiyanti, Dwi; Purwati, Dwi; Amalia, Wafi; Azmil, Rosidah; Syifa, Annisa; Zaldrin, Aegis; Maharani, Alivia (Edumedia Solution, 2023)
Tofu is raw food made from soybean. It takes 2 -3 hours to process the soybean until finish. The workshop aimed to discuss with the owner of tofu factory that it will be dregs into further process to be snack with higher value. The method used is mentoring and socialization of programs for one month in the community, the workshop then begins with cooking process, by authors. Then, the companion aldo held from process of tax civil number (NPWP), number Business Registration Number (NIB),Â until the companion of making account in digital marketing and packaging. Tofu will be sold through online shopping platform by the means of halal-licensed for this tofu snacks. So far, people only process tofu which served as dishes and tofu reside then isnâ€™t been process, directed to sell . In fact, the kind of production is just make little sum of money for the factory owner. This workshop has goals to increase their income. Based on community empowerment to process the tofu reside. Thus, the result from this workshop and accompaniment will be beneficial for community in the Cerme hamlet who have been relying on agricultural products with three harvests a year. Further, people will no longer depend on agricultural products but they can tofu dregs into high-value preparations with the creativity of these processing, such as tofu chips, tofu crackers and tofu sticks.